Receptor Interactions of Angiotensin II and Angiotensin Receptor Blockers—Relevance to COVID-19 - Moore, Graham J. (Biomolecules, 2021)
Angiotensin II (Ang II) may contain a charge relay system (CRS) involving Tyr/His/carboxylate, which creates a tyrosinate anion for receptor activation. Energy calculations were carried out to determine the preferred geometry for the CRS in the presence and absence of the Arg guanidino group occupying position 2 of Ang II. These findings suggest that Tyr is preferred over His for bearing the negative charge and that the CRS is stabilized by the guanidino group. Recent crystallography studies provided details of the binding of nonpeptide angiotensin receptor blockers (ARBs) to the Ang II type 1 (AT1) receptor, and these insights were applied to Ang II. A model of binding and receptor activation that explains the surmountable and insurmountable effects of Ang II analogues sarmesin and sarilesin, respectively, was developed and enabled the discovery of a new generation of ARBs called bisartans. Finally, we determined the ability of the bisartan BV6(TFA) to act as a potential ARB, demonstrating similar effects to candesartan, by reducing vasoconstriction of rabbit iliac arteries in response to cumulative doses of Ang II. Recent clinical studies have shown that Ang II receptor blockers have protective effects in hypertensive patients infected with SARS-CoV-2. Therefore, the usage of ARBS to block the AT1 receptor preventing the binding of toxic angiotensin implicated in the storm of cytokines in SARS-CoV-2 is a target treatment and opens new avenues for disease therapy.